Taṭwīr Mawād al-Qirā’ah Bi al-Wasā’il al-Muta`addidah at-Tafā`uliyah (Dirāsah al-Baḥṡ Wa at-Taṭwīr Li al-Marḥalah al-Mutawassiṭah Bi Ma`had Bāb al-Maghfirah Aceh Besar) - Fadhil H. Nurdin; Ahmad Fauzi; Badruzzaman Badruzzaman (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
The researcher has noticed a manifestation of the incident that most teachers from the middle school at the SMP Babul Maghfirah use traditional educational means in the process of teaching Arabic, especially for reading skills, and read and translate the material from the textbook until they need a long opportunity to repeat the reading text, and the text may read a dispute about exits The letters, and on this, it is difficult for students to focus, hear and understand the contents of the reading story what the teacher read from the textbook because many of the students are graduates of the SDN primary school and they did not learn Arabic before, as well as they still do not control the many vocabularies. Therefore, the researcher wants to do research on the development of Reading Subject Matter Based on Interactive Multimedia (Research and Development at SMP Babul Maghfirah in Aceh Besar). The research aims to develop Reading Subject Matter Based on Interactive Multimedia and its effects on students. The research method referred to research and development using the method named ADDIE. The research population includes all students of Babul Maghfirah in Aceh Besar, 28 students from the second grade (D), and 432 students in total. The researcher has conducted interviews, questionnaires, and tests as research tools. This research aims to develop interactive Multimedia that could give more positive benefits to students based on five steps; analysis, design, development, application, and evaluation. As a result, the researcher has successfully created a new interactive Multimedia of reading subject matter. It also has received a positive score, in learning materials and media 100% (Special). The application has effectively contributed to the development of students reading ability based on the calculation (t-test), which is bigger than the table's results (t-table) or 7.76 > 2.05 and 2.77.